Protocol for the SAFEST review: the Shock-Absorbing Flooring Effectiveness SysTematic review including older adults and staff in hospitals and care homes. Issue 2 (17th February 2020) - Drahota, Amy; Felix, Lambert M; Keenan, Bethany E; Lachance, Chantelle C; Laing, Andrew; Mackey, Dawn C; Raftery, James
Abstract : Introduction: Falls in hospitals and care homes are a major issue of international concern. Inpatient falls are the most commonly reported safety incident in the UK's National Health Service (NHS), costing the NHS £630 million a year. Injurious falls are particularly life-limiting and costly. There is a growing body of evidence on shock-absorbing flooring for fall-related injury prevention; however, no systematic review exists to inform practice. Methods and analysis: We will systematically identify, appraise and summarise studies investigating the clinical and cost-effectiveness, and experiences of shock-absorbing flooring in hospitals and care homes. Our search will build on an extensive search conducted by a scoping review (inception to May 2016). We will search electronic databases (AgeLine, CINAHL, MEDLINE, NHS Economic Evaluation Database, Scopus and Web of Science; May 2016–present), trial registries and grey literature. We will conduct backward and forward citation searches of included studies, and liaise with study researchers. We will evaluate the influence of floors on fall-related injuries, falls and staff work-related injuries through randomised and non-randomised studies, consider economic and qualitative evidence, and implementation factors. We will consider risk of bias, assess heterogeneity and explore potential effect modifiers via subgroup analyses and sensitivity analyses. Where appropriate we will combine studies through meta-analysis. We will use the GRADE (Grading of Recommendations, Assessment, Development and Evaluations) approach to evaluate the quality of evidence and present the results using summary of findings tables, and adhere to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses reporting guidelines. Ethics and dissemination: We will follow the ethical principles of systematic review conduct, by attending to publication ethics, transparency and rigour. Our dissemination plan includes peer-reviewed publication, presentations, press release, stakeholder symposium, patient video and targeted knowledge-to-action reports. This review will inform decision-making around falls management in care settings and identify important directions for future research. PROSPERO registration number: CRD42019118834.